Ecosystem recovery indicators as decision criteria on potential reduction of fallow periods in swidden systems of Northern Thailand. (December 2018) - Tongkoom, K.; Marohn, C.; Piepho, H.P.; Cadisch, G.
Highlights: Indicators sought for sustainably reducing fallow periods in swidden cultivation. Stand structure and tree diversity-related parameters were assessed. Criterion for fallow reduction: Transgression of a peak within current fallow period. Approach applicable across sites, but requiring site-specific parameters. Reference site of climax vegetation adds to robustness of approach. Abstract: Crop rotations in today's swidden systems of Northern Thailand typically include five to ten years of fallow. Regarding ecosystem functions, these systems are relatively close to secondary forests when compared to modern agricultural systems; but they are under pressure for intensification, i.e. shortened fallow periods. In general, criteria are needed to decide whether fallow duration can be reduced, safeguarding ecosystem restoration and provision of food and income for farmers. Acknowledging that a comprehensive assessment would cover multiple aspects, our study focuses on the role of fallow duration on tree structural and biodiversity related variables. We studied recovery indicators of tree communities at two potential broad-leaved forest climax sites that differ in soils, forest type and agricultural intensification: An intensive system of one-year upland rice, then one- to two-year maize cultivation with synthetic inputs followed by six years fallow; and an extensive system with one-year upland rice cultivation without agrochemicals and ten years fallow. Contrasting systems were chosen to test the applicability of our indicators, not to compare their management practices. From 2010 to 2011, eight variables related to stand structure and tree diversity were either monitored or surveyed in chronosequence plots of 6 × 50 m representing different fallow ages. For each variable, means per fallow year were compared by least squares means (LS-means), and quadratic regressions from mixed models were fitted. Significant differences between LS-means and optima of regressions served to distinguish fallow stages and served as indicators of recovery and system stability. Stepwise multiple regressions confirmed fallow age as main determinant for most variables. Numbers of tree species and diversity index recovered to levels of the previous rotation within the respective fallow time, but in both systems were far from climax communities, probably due to seed-bank depletion and shift toward resprouting species. While species dominance changed over time in the extensive system, the intensive system was dominated by a single species. In the extensive system only tree density passed a peak during the fallow period, while biomass-related variables approached plateaus. In combination with the replacement of early fallow species, this points to the onset of competition and transition between successional stages. For the intensive system, no structural variable passed a maximum. With only one of eight indicators on the extensive site fulfilling the statistical criterion of passing a peak during the prevailing fallow time, reducing fallow periods is not recommended for our cases. Generally, combining LS-means and quadratic regression allowed assessing fallow duration based on distinct successional stages at different sites. The approach should include various relevant site-specific indicators, in our case representing biomass and carbon storage, species and structural diversity, considered crucial for both sites.